Structure design and experimental study on single-bimorph double-acting check-valve piezoelectric pump. (August 2016) - Zeng, Ping; Li, Li'an; Dong, Jingshi; Cheng, Guangming; Kan, Junwu; Xu, Feng
A novel piezoelectric pump called single-bimorph double-acting check-valve piezoelectric pump was proposed in this paper in order to improve the output performance of the single-bimorph single-chamber piezoelectric membrane pump. The constituent parts of the newly designed piezoelectric pump have no difference with the single-bimorph single-chamber check-valve piezoelectric membrane pump except the structural difference of the pump body. There are two serial-connection pump chambers which are formed by the two sides of the piezoelectric bimorph and the pump body of the newly designed piezoelectric pump. The new piezoelectric pump was fabricated, and output performance was experimentally investigated. The maximum flow rate against zero back pressure of the new pump was 318 ml/min and the pumping pressure reached 40.5 kPa at the operating voltage of 90 V. The output power was roughly twice that of the single-bimorph single-chamber check-valve piezoelectric membrane pump. The testing results proved that the new piezoelectric pump could enhance the output performance and the energy conversion efficiency of the piezoelectric bimorph comparing with the single-bimorph single-chamber check-valve piezoelectric membrane pump.